Hydraulic conductivity of novel geosynthetic clay liner to bauxite liquor from China: Modified fluid loss test evaluation. (15th August 2022) - Yang, Yu-Ling; You, Xing-Yuan; Chen, Jian-Nan; Fu, Xian-Lei; Du, Yan-Jun
Abstract: A modified sodium bentonite geosynthetic clay liner (GCL) designed for acid-and-alkaline resistance was evaluated for its potential application in the containment of bauxite residue leachate. A modified fluid loss test was employed to quickly evaluate the hydraulic conductivity ( k ) of the GCL using distilled water, tap water, and four bauxite liquors (BLs, leachate from bauxite residue reservoirs). The effects of swelling capacity of bentonite, prehydration, hydraulic gradient ( i ), ionic strength ( I ), and relative abundance of monovalent and multivalent cations ( RMD ) on the hydraulic conductivity of the GCL were analyzed. The results indicated that the BLs significantly decreased free swell index of the bentonite. As compared to increasing i, prehydration obviously enhanced hydraulic performance of the GCL. The four BLs increased k of the GCL by a factor of 4–12 relative to the tap water permeation condition, and the resultant k exceeded upper limit of 5.0 × 10 −11  m/s for GCLs. The increase in k was attributed to compression in diffuse double layer of the bentonite and dissolution in clay minerals in ion-rich and hyperalkaline BLs, manifesting that further modification on the GCL is needed. The I was found a better indicator than the RMD on correlation with chemical compatibility of the GCL. Highlights: Bauxite liquors deteriorated swelling capacity and permeability of the GCL. Diffuse double layer compression and clay mineral dissolution caused chemical incompatibility. Prehydration and high hydraulic gradient contributed to reduce hydraulic conductivity. Ionic strength was the superior factor influenced hydraulic conductivity of GCL.